Perlindungan Hukum Bagi Pekerja Digital Freelance Di Era Transformasi Digital - Lily Marheni; I Gusti Ayu Widiadnyani; I Nyoman Bagiastra; Muhammad Panji Mahardika (Universitas Cokroaminoto Yogyakarta, 2026)
The purpose of this study is to determine the legal status of freelance digital workers in the Indonesian employment system and the legal protections that can be implemented to improve the welfare of freelance digital workers in the era of transformation. The results of the study indicate that the existence of freelance digital workers has not yet received clear legal recognition in the national employment system. Most of them are still categorized as informal workers or work partners, not as workers in an employment relationship as regulated in the Manpower Law Number 13 of 2003. Legal recognition of the status of freelance digital workers can be the basis for determining special worker categories such as platform workers or digital independent workers, then providing access to basic protections such as social security, employment insurance and requiring digital platforms to be responsible for the working conditions of their workers.